Decoding Pedophilia: Increased Anterior Insula Response to Infant Animal Pictures - Ponseti, Jorge; Bruhn, Daniel; Nolting, Julia; Gerwinn, Hannah; Pohl, Alexander; Stirn, Aglaja; Granert, Oliver; Laufs, Helmut; Deuschl, Günther; Wolff, Stephan; Jansen, Olav; Siebner, Hartwig; et al. (Frontiers in Human Neuroscience, 2018)
Previous research found increased brain responses of men with sexual interest in children (i.e. pedophiles) not only to pictures of naked children but also to pictures of child faces. This opens the possibly that pedophilia is linked (in addition to or instead of an aberrant sexual system) to an over-active nurturing system. To test this hypothesis we exposed pedophiles and healthy controls to pictures of infant and adult animals during functional magnetic resonance imaging of the brain. By using pictures of infant animals (instead of human infants) we aimed to elicit nurturing processing without triggering sexual processing. We hypothesized that elevated brain responses to nurturing stimuli will be found – in addition to other brain areas – in the anterior insula of pedophiles because this area was repeatedly found to be activated when adults see pictures of babies. Behavioral ratings confirmed that pictures of infant or adult animals were not perceived as sexually arousing neither by the pedophilic participants nor by the heathy controls. Statistical analysis was applied to the whole brain as well as to the anterior insula as region of interest. Only in pedophiles did infants relative to adult animals increase brain activity in the anterior insula, supplementary motor cortex, and dorsolateral prefrontal areas. Within-group analysis revealed an increased brain response to infant animals in the left anterior insular cortex of the pedophilic participants. Currently, pedophilia is considered the consequence of disturbed sexual or executive brain processing, but details are far from known. The present findings raise the question whether there is also an over-responsive nurturing sys-tem in pedophilia.